5′ Nuclease PCR Assay To Detect Yersinia pestis - Higgins, James A. (American Society for Microbiology, 1998)
The 5′ nuclease PCR assay uses a fluorescently labeled oligonucleotide probe (TaqMan) to rapidly detect and quantitate DNA templates in clinical samples. We developed a 5′ nuclease PCR assay targeting the plasminogen activator gene (pla) of Yersinia pestis. The assay is species specific, with a detection threshold of 2.1 × 10(5) copies of the pla target or 1.6 pg of total cell DNA. The assay detected Y. pestis in experimentally infected Xenopsylla cheopis fleas and in experimentally infected monkey blood and oropharyngeal swabs. The TaqMan assay is simple to perform and rapid and shows promise as a future field-adaptable technique.